Unravelling Functional Neurology: an overview of all published documents by FR Carrick, including a critical review of research articles on its effect or benefit - Demortier, Marine (Chiropr Man Therap, 2020)
BACKGROUND: Functional Neurology (FN), founded by FR Carrick, is an approach used by some chiropractors to treat a multitude of conditions via the nervous system including the brain. However, it seems to lack easily obtainable scientific evidence for its clinical validity. OBJECTIVES: 1) To define the topics of FR Carrick’s publications, 2) to define the proportion of articles that are research studies, case studies, abstracts and conference papers, 3) to define how many of these are clinical research studies that purported or appeared to deal with the effect or benefit of FN, 4) in these studies, to establish whether the design and overall study method were suitable for research into the effect or benefit of FN, and 5) to describe the evidence available in relation to the clinical effect or benefit of FN, taking into account seven minimal methodological criteria. METHOD: A literature search was done on Pubmed from its inception till October 2018, supplemented by a search on Scopus and ResearchGate to find all published documents by FR Carrick. We identified their types and topics, retaining for a critical review full text scientific articles appearing to test effect/benefit of FN procedures, subjecting them to a basic quality assessment (scoring 0–7). Results from studies of methodologically acceptable standard would be taken into account. RESULTS: We found 121 published texts, 39 of which were full scientific research articles. Of these, 23 dealt with topics relating to FN. Fourteen articles reported on clinical validity but only seven included a control group. The methodological quality of these seven articles was low, ranging between 1.5–4 out of 7. We therefore did not further report the outcomes of these studies. CONCLUSION: We found no acceptable evidence in favour of effect/benefit of the FN approach. We therefore do not recommend its promotion as an evidence-based method. Further research on this topic should be conducted in collaboration with independent scientific institutions using commonly accepted research methods. TRIAL REGISTRATION: PROSPERO This review was registered in PROSPERO (application date 23.02.2019; no CRD42019126345).